2013
DOI: 10.2224/sbp.2013.41.4.529
|View full text |Cite
|
Sign up to set email alerts
|

How internal marketing can cultivate psychological empowerment and enhance employee performance

Abstract: We examined the impact of psychological empowerment on employee loyalty, satisfaction, and task performance with survey data from 617 employees of a petrochemical company in China. Results based on a structural equation model showed that psychological empowerment had a significant positive effect on both employee loyalty and task performance, which was partially mediated by employee satisfaction. In addition, we found that psychological empowerment was significantly and positively influenced by each dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
4
25
0
4
Order By: Relevance
“…The second most studied concept of empowerment in organizational context is termed as psychological empowerment (Spreitzer, 1995). Many studies have found psychological empowerment to be also related to desired organizational objectives such as organizational citizenship behavior (Aksel et al, 2013), employee performance (Yao, Chen and Cai, 2013), organizational learning (Safari et al, 2011) and interpersonal trust (Moye, Henkin and Egley, 2005). One of the most important desired organizational attitudes is employee commitment that leads toward achievement of organizational goals.…”
mentioning
confidence: 99%
“…The second most studied concept of empowerment in organizational context is termed as psychological empowerment (Spreitzer, 1995). Many studies have found psychological empowerment to be also related to desired organizational objectives such as organizational citizenship behavior (Aksel et al, 2013), employee performance (Yao, Chen and Cai, 2013), organizational learning (Safari et al, 2011) and interpersonal trust (Moye, Henkin and Egley, 2005). One of the most important desired organizational attitudes is employee commitment that leads toward achievement of organizational goals.…”
mentioning
confidence: 99%
“…Estos resultados están en línea con los observados en otras investigaciones (Cicolini et al, 2013;Lautizi et al, 2009;Orgambídez-Ramos et al, 2014;Spreitzer et al, 1997;Yao, 2013). Spreitzer et al (1997), con dos muestras de empleados norteameri canos, una de supervisores y otra de empleados de base, observaron igualmente que el significado y la autodeterminación fueron predic tores significativos de la satisfacción, mientras que la competencia y el impacto de relacionaron más con la eficacia y el desempeño en el trabajo.…”
Section: Discussionunclassified
“…En los estudios de Orgambídez-Ramos et al (2014) y Lautizi et al (2009, el empowerment fue predictor significativo y positivo de la satisfacción laboral en muestras de docentes y de personal de enfer mería. En la investigación de Yao (2013), el significado también fue la dimensión del EP con mayor peso sobre la satisfacción laboral.…”
Section: Discussionunclassified
See 2 more Smart Citations